1,2(1,25)$9(Perform the indicated operation.) $42(No, that's incorrect. Try again.HINT: )$43($4255Add the opposite of -2, or 2.)$46($4255Subtraction is the same as adding the opposite. Check your calculation.) n(1=2)
3(1e2+)
$91:2 - (-2) = ? i11:2 - (-2) = ? Instead of subtracting -2, we c2ADDc0 the c2OPPOSITEc0, which would be 2.= 1 + (2)p= 3
3#1-2@$43_$46
1,2(-25,-1)$9(Perform the indicated operation.)$42(No, that's incorrect. Try again.HINT: ) $43($4255Add the opposite of 2, or 4.)$46($4255Subtraction is the same as adding the opposite. Check your calculation.) n(1=2)
3(2i1+)4(2i)
$91:3 - (2) = ? i11:3 - (2) = ? Instead of subtracting 2, we c2ADDc0 the c2OPPOSITEc0, which would be 4.= 1 + (4)p= 3
3#1+2@$43_$46
1(-25,-1)2(1,25)$9(Perform the indicated operation.)$42(No, that's incorrect. Try again.HINT: ) $43($4255Add the opposite of 2, or -2.)$46($4255Subtraction is the same as adding the opposite. Check your calculation.)
3(1e2-)
$91 - 2 = ? i11 - 2 = ? Instead of subtracting 2, we c2ADDc0 the c2OPPOSITEc0, which would be -2.= 1 + (-2)p= 3
3#1+2@$43_$46
1(-25,-1)2(1,25)$9(Perform the indicated operation.)$42(No, that's incorrect. Try again.HINT: ) $43($4255Add the opposite of 2, or -2.)$46($4255Subtraction is the same as adding the opposite. Check your calculation.)
3(1e2-)
$91 - 2 = ? i11 - 2 = ? Instead of subtracting 2, we c2ADDc0 the c2OPPOSITEc0, which would be -2.= 1 + (-2)p= 3
3#1+2@$43_$46
1(12,50)$9(Perform the indicated operation.)$42(No, that's incorrect. Try again.HINT: ) $43($4255Add the opposite of -1, or 1.)$46($4255Subtraction is the same as adding the opposite. Check your calculation.)
?
$90 - (-1) = ? i1a0 - (-1) = ? Instead of subtracting -1, we c2ADDc0 the c2OPPOSITEc0,which would be 1.p40 - (-1) = 0 + 113 = 1
1#-1@$43_$46
1,2(1,15)3(1,9) $42(No, that's incorrect. Try again.HINT: )$46($4255Use correct order of operations. Check your calculations and the sign of your answer.)
4(2e3+i1+)5(2e3+)n(4=0)
Perform the indicated operations.1 - [2 - (-3)] = ? i11:2 - [2:2 - (-3)] = ? First we perform the operations inside the brackets. Change the subtraction to adding the opposite.= 1 - [2 + (3)]p= 1 - [5]pChange the subtraction to adding the opposite.= 1 + (-5)p= 4p
4_$46
1(-15,-1)2(1,15)3(1,9)$42(No, that's incorrect. Try again.HINT: )$46($4255Use correct order of operations. Check your calculations and the sign of your answer.)
4(2e3+i1+)5(2e3+)n(4=0)
Perform the indicated operations.1 - [2 - (-3)] = ? i11:3 - [2:2 - (-3)] = ? First we perform the operations inside the brackets. Change the subtraction to adding the opposite.= 1 - [2 + (3)]p= 1 - [5]pChange the subtraction to adding the opposite.= 1 + (-5)p= 4p
4_$46
1,2(-15,-1)3(1,9)$42(No, that's incorrect. Try again.HINT: )$46($4255Use correct order of operations. Check your calculations and the sign of your answer.)
4(1e2-3-)5(1e2-)6(2ei)n(4=0)
Perform the indicated operations.[(1) - (2)] - 3 = ? i1[(1) - (2)] - 3 = ? First we perform the operations inside the brackets. Change the subtraction to adding the opposite.= [(1) + (6)] - 3p= [5] - 3pChange the subtraction to adding the opposite.= [5] + (-3)p= 4p
4_$46
1,2,4,5(-15,-1)3,6(1,15)$42(No, that's incorrect. Try again.HINT: )$46($4255Use correct order of operations. Check your calculations and the sign of your answer.)
Perform the indicated operations.[1 + (2)] - [3 + (4)] - [5 + 6] = ? i1[1 + (2)] - [3 + (4)] - [5 + 6] = ? First we perform the operations inside the brackets. Begin with the leftmost set of brackets and work to the right.= [8] - [3 + (4)] - [5 + 6]p= [8] - [9] - [5 + 6]p= [8] - [9] - [10]pChange the subtraction to adding the opposite.= [8] + [12] + [13]= 11 + [13]p= 14p
14_$46
1(1,2)$1(positive)$2(negative)
2(3e1-)
If c2ac0 is a $2 number and c2bc0 is a $1number, then will c2ac0 - (-c2bc0 + c2bc0) be positive ornegative?i2If c2ac0 is a $2 number and c2bc0 is a $1number, then will c2ac0 - (-c2bc0 + c2bc0) be positive ornegative?To calculate a - (-b + b) first we performthe operation inside the parentheses. Therewe have the sum of a number, -b and its opposite,b. This sum is equal to zero.Then,3a - (-b + b) 5= a - (0)5= a,which we assumed to be $2.p